Including people with intellectual and other cognitive disabilities in research and evaluation teams: A scoping review of the empirical knowledge base - Ghaderi, Golnaz; Milley, Peter; Lysaght, Rosemary; Cobigo, Virginie (Journal of intellectual disabilities, 2025)
We conducted a rapid scoping review of empirical studies to identify how persons with intellectual and other cognitive disabilities have been engaged as active members of research and evaluation teams. We conducted a literature search using a systematic method that accessed peer reviewed studies in relevant library databases and all major evaluation journals. The search resulted in 6,624 potential articles, of which 32 met the inclusion criteria for this study. The findings address three categories of interest: 1) methodological underpinnings and practical justifications for using inclusive approaches, 2) different inclusion processes, and 3) reflections by researchers with and without intellectual and other cognitive disabilities. Findings provide conceptual and practical insights for researchers and evaluators when designing inclusive methods involving persons with intellectual and other cognitive disabilities. Gaps in inclusive research and evaluation are discussed and suggestions for future research are proposed.